Exploring the Theory of State Sovereignty over Stratatitle and Marine Cadastre Regulations as Instruments for Protecting Spatial Rights - Isep H Insan; Nazaruddin Lathif (Faculty of Law, Universitas Pekalongan, 2025)
The urgency of regulating strata title and marine cadastre in Indonesia is increasingly important in line with rapid urbanization and the need for sustainable marine spatial management. This study aims to analyze the application of state sovereignty theory in the regulation of vertical and marine space, as well as to propose a more comprehensive and integrated legal framework. This approach is expected to identify normative solutions to strengthen the protection of rights to space and prevent ownership conflicts or regulatory overlaps. Through this study, it is hoped that clearer and fairer regulations on the utilization of vertical and marine space in Indonesia can be achieved. The research method used is normative juridical, analyzing legislation, legal doctrines, and state sovereignty theory to explore existing legal gaps and regulatory fragmentation. This study finds that state sovereignty plays an important role in the regulation of vertical and maritime space through regulations that ensure space management is carried out in an orderly, fair, and sustainable manner. Through the Marine Cadastre, the state can strengthen legal certainty and marine spatial management in accordance with national policies outlined in Law No. 32 of 2014 on Marine Affairs. Despite challenges in implementation, effective coordination among government agencies and international cooperation are essential to support sustainable development and the protection of natural resources.